Assessment of Water Quality in Surface Water of Shipbreaking Sites at Kumira Ghat, Sitakunda, Bangladesh - Rezuana Afrin; Sydur Rahman Gazi; Abu Abdulla Al-Mamun; Md. Hossain Khan; Muliadi Muliadi; Shamim Al Mamun (TECHNO: JURNAL PENELITIAN, 2021)
The Bay of Bengal ecosystem is blessed with vast resources. A major part of the people living nearby coastal areas depends on marine resources for their livelihood. These resources are facing risks due to pollution caused by shipbreaking activities. The present study was conducted to investigate the water quality adjacent to shipbreaking sites of Kumira Ghat, Sitakunda, Chittagong, Bangladesh and was carried out by field measurements of DO, pH, TDS, EC, temperature; BOD and heavy metals (Cd, Pb, Hg, Cu and Fe) in the laboratory while heavy metals followed by Atomic Absorption Spectrometry (AAS) methods of 5 water samples. The values of DO, pH, TDS, EC, BOD and temperature ranged from 7.16 to 7.43 mg/l, 8.02 to 8.04, >10000 mg/l, 5752 to 6745 µS/cm, 1.4 to 2.76 mg/l, 26.87 to 27.6 ºC, respectively. The values of Temperature, pH and BOD were within the standard limit but TDS and EC values were exceeding the standard level given by WHO for surface water. According to the study, the water was contaminated with Cd (0.003 to 0.007 mg/l), Pb (0.01 mg/l), Hg (<0.001), Cu (<0.1 mg/l) and Fe (25.2 to 53.6 mg/l). The amount of Fe crossed the standard level for surface water (0.1-1.0 mg/l) given by WHO. Finally, it was found that water was alkaline based on pH range. The ionization capacity of the water was very high because of high TDS and EC values. Positive correlations were found among pH and Temperature, BOD and Temperature, BOD and pH, Fe and EC and negative correlations were found among EC and Temperature, EC and BOD, Fe and Temperature and Fe and BOD.